2020
DOI: 10.1158/1078-0432.ccr-20-0400
|View full text |Cite
|
Sign up to set email alerts
|

Potent Activity of an Anti-ICAM1 Antibody–Drug Conjugate against Multiple Myeloma

Abstract: Purpose: New therapies have changed the outlook for patients with multiple myeloma, but novel agents are needed for patients who are refractory or relapsed on currently approved drug classes. Novel targets other than CD38 and BCMA are needed for new immunotherapy development, as resistance to daratumumab and emerging anti-BCMA approaches appears inevitable. One potential target of interest in myeloma is ICAM1. Naked anti-ICAM1 antibodies were active in preclinical models of myeloma and safe i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…CD24 is a highly expressed, anti-phagocytic signal in several cancers and demonstrates therapeutic potential for CD24 blockade in cancer immunotherapy [68]. ICAM-1 antibodies showed potent anti-myeloma activity in multiple studies [69] [70] [71]. CD44 mediates resistance to lenalidomide in multiple myeloma [72], and CD44-targeted T cells mediate potent anti-tumour effects against multiple myeloma [73].…”
Section: Discussionmentioning
confidence: 99%
“…CD24 is a highly expressed, anti-phagocytic signal in several cancers and demonstrates therapeutic potential for CD24 blockade in cancer immunotherapy [68]. ICAM-1 antibodies showed potent anti-myeloma activity in multiple studies [69] [70] [71]. CD44 mediates resistance to lenalidomide in multiple myeloma [72], and CD44-targeted T cells mediate potent anti-tumour effects against multiple myeloma [73].…”
Section: Discussionmentioning
confidence: 99%
“…Precision medicines as well as biotherapeutic agents, including therapeutic monoclonal antibodies such as the anti-CD38 MoAb Daratumumab and isatuximab, and the anti-signaling lymphocyte activation marker F7, antibody elotuzumab, antibody-drug conjugates, and bispecific antibodies (BiAb) have been developed to damage drug-resistant MM clones as well as alter the immunosuppressive bone marrow microenvironment with some very promising clinical data regarding their clinical impact potential [ 1 , 4 , 39 ] . T-cell redirecting BiAb and bispecific T-cell engagers (BiTES) targeting CD38, the orphan G protein-coupled receptor GPRC5D, and the B-cell maturation antigen (BCMA)/CD269 on MM cells and CD3 antigen on T-cells facilitate the CTL-mediated destruction of drug-resistant MM cells in cytolytic synapses [ 4 , 40 ] .…”
Section: Main Textmentioning
confidence: 99%
“…Naked anti-ICAM1 antibodies were active in preclinical studies and safe in myeloma patients but showed limited clinical efficacy; thus, an anti-ICAM1 ADC was developed for better targeting MM cells. Potent anti-myeloma cytotoxicity was displayed by anti-ICAM1 ADC in vitro and in vivo [ 69 , 70 ]. In a study conducted by Hansson et al (NCT010252060), BI-505, a human anti-ICAM-1 mAb, was evaluated for safety and tolerability in advanced RRMM patients.…”
Section: Antibody-drug Conjugates (Adc)mentioning
confidence: 99%